2017
DOI: 10.1016/j.renene.2016.10.049
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the condition of Marine Renewable Energy Devices through underwater Acoustic Emissions: Case study of a Wave Energy Converter in Falmouth Bay, UK

Abstract: Maintaining the engineering health of Marine Renewable Energy Devices (MREDs) is one of the main limits to their economic viability, because of the requirement for costly marine interventions in challenging conditions. Acoustic Emission (AE) condition monitoring is routinely and successfully used for land-based devices, and this paper shows how it can be used underwater. We review the acoustic signatures expected from operation and likely failure modes of MREDs, providing a basis for a generic classification s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…This was briefly described in Section 2.2 and is fully detailed in Walsh et al 2016. The acoustic signature was broadband (100 Hz -1 kHz) with tonal components at 30, 60, 80 and 100 Hz.…”
Section: Comparison Of Modelling Conditions: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This was briefly described in Section 2.2 and is fully detailed in Walsh et al 2016. The acoustic signature was broadband (100 Hz -1 kHz) with tonal components at 30, 60, 80 and 100 Hz.…”
Section: Comparison Of Modelling Conditions: Resultsmentioning
confidence: 99%
“…Detailed time-frequency analyses showed that the AE signature of the active PTO system during the WEC operation were 0.5-second duration bursts up to 90 dB loud, mostly between 100 Hz and 1 kHz. Loud tonal components at 30, 60, 80 and 100 Hz, reaching 90 dB were also recorded and attributed to the device generator (Walsh et al 2016). Table 1.…”
Section: Measurements and Observationsmentioning
confidence: 93%
See 3 more Smart Citations